The Location of AIDS - Aaron Muldoon (University of Edinburgh, 2021)
We could easily characterise the emergent field of posthumanism as a critique of various forms of boundary. For instance, posthumanism casts its critical eye on the boundary between human and nonhuman and the boundary between what counts as the body and what does not. The biomedical discourse on AIDS—and on immunology in general—is profoundly shaped by the imposition and reinforcement of various boundaries and distinctions. Foremost amongst these are the boundary between the body and infection and the distinction between different types of bodies (black/white, gay/straight). The following essay explores the subversive potential of applying a posthumanist critique of boundaries and distinctions to the discourse on AIDS and its representations, with a particular focus on those found in Essex Hemphill’s poem “Vital Signs”.